APLIKASI SISTEM INFORMASI KULINER DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA BERBASIS ANDROID - Oktavina Marlina Roma; Uning Lestari; Naniek Widyastuti (Jurnal SCRIPT, 2015)
Culinary is the main need of everyone. Culinary development now makes all difficult to determine what will be selected. With the application of this culinary information system, enables consumers to make choices in culinary his liking. With no Google Maps and GPS, consumers can more easily to view the location of the nearest culinary desired while in the city of Yogyakarta. In these applications, requiring culinary names, pictures of culinary, culinary venue, address and location of the nearest of the consumer. The support tools are in use is PHP, mySQL, android SDK. This app uses the android phone features such as GPS, 3G and wifi, and other supporting applications is google maps to get the shortest route, distance and time from the consumer.